Terahertz Nondestructive Time-of-flight Imaging with a Large Depth Range - Kim, Hwan Sik; Kim, Jangsun; Ahn, Yeong Hwan (Current Optics and Photonics, 2022)
In this study, we develop a three-dimensional (3D) terahertz time-of-flight (THz-TOF) imaging technique with a large depth range, based on asynchronous optical sampling (ASOPS) methods. THz-TOF imaging with the ASOPS technique enables rapid scanning with a time-delay span of 10 ns. This means that a depth range of 1.5 m is possible in principle, whereas in practice it is limited by the focus depth determined by the optical geometry, such as the focal length of the scan lens. We characterize the spatial resolution of objects at different vertical positions with a focal length of 5 cm. The lateral resolution varies from 0.8–1.8 mm within the vertical range of 50 mm. We obtain THz-TOF images for samples with multiple reflection layers; the horizontal and vertical locations of the objects are successfully determined from the 2D cross-sectional images, or from reconstructed 3D images. For instance, we can identify metallic objects embedded in insulating enclosures having a vertical depth range greater than 30 mm. For feasible practical use, we employ the proposed technique to locate a metallic object within a thick chocolate bar, which is not accessible via conventional transmission geometry.
Keywords: Asynchronous optical samplings; Depth range; Focal lengths; Metallic objects; Non destructive; Range-based; Tera Hertz; Terahertz spectroscopy and imaging; Three dimensional imaging; Time-of-flight imaging; Terahertz spectroscopy and imaging; Three-dimensional imaging